Goodwill: Accounting, Assessment and Auditing - Lubenchenko О. Е. (Statistics of Ukraine, 2023)
The accounting of goodwill is an integral part of the transactions on business mergers and acquisitions. An analytical review of the definitions of the notions “asset” and “goodwill” was made. It revealed that goodwill was not a “classical” asset, because it could not be separated from a business entity. As investors, business managers and auditors have the need in its assessment, e. g. by evidence-based methods of goodwill assessment, such as balance method, business activity method, excess earnings method or expert assessment. The goodwill depreciation test is complicated and performed through assessing the capabilities of a company or its units to generate monetary flows. It is emphasized due the pandemic of COVID-19 leading European companies had to recognize goodwill devaluation in their financial reports in 2020–2021. The assessment of goodwill is a subject of auditor’s concern. The factors devaluating the assets, goodwill in particular, including the ones caused by the martial law, were systematized and supplemented, the working document of an auditor for the goodwill devaluation test was elaborated. In parallel with the goodwill devaluation test, an auditor is recommended to perform assessment of the company’s operation continuity, which will also confirm or deny the opinion about asset devaluation; a working document that considers for financial, operational and other factors of utility loss is proposed. The working documents are universal and can essentially simplify the documenting of auditing procedures. Based on a review of the International Standards on Auditing, the author came to the conclusion that the goodwill testing would not be always the key issue of audit. When an auditor does not agree with the estimates of goodwill depreciation made by accounting personnel and this disagreement is material, he will have to modify his report by articulating an opinion with reservation or a negative opinion, or by abstaining from giving his opinion.